The Satisfaction with Life Scale: Philosophical Foundation and Practical Limitations - Kusier, Amalie Oxholm; Folker, Anna Paldam (Health care analysis, 2021)
Research and policymaking on positive mental health and well-being have increased within the last decade, partly fueled by decreasing levels of well-being in the general population and among at-risk groups. However, measurement of well-being often takes place in the absence of reflection on the underlying theoretical conceptualization of well-being. This disguises the fact that different rating scales of well-being often measure very different phenomena because rating scales are based on different philosophical assumptions, which represent radically different foundational views about the nature of well-being. The aim of this paper is to examine the philosophical foundation of the Satisfaction with Life Scale (SWLS) in order to clarify the underlying normative commitments and the psychometric compromises involved in the translation of theory into practice. SWLS is widely used by psychologists, public health professionals, economists, and is popular in national and international surveys of well-being. This paper introduces the philosophical theory of life satisfaction and explores how three central discussions within life satisfaction theory are reflected in the construction of the SWLS; (1) Whether we should be equally satisfied with our past, present and future, (2) Whether we should be satisfied with all the various domains of our lives, and (3) How to avoid the trap of “false consciousness”, i.e. that people fail to recognize the injustice or misfortune of their lives. In the end, life satisfaction theory is contrasted with affective foundational theories of well-being, to explore the magnitude and limits of SWLS as a rating scale based on life satisfaction theory.